Indonesian Student Fitness Test to Measure Students Physical Fitness Levels - Lestari, Riska; Destriana, Destriana; Destriani, Destriani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The aim of this research is to determine the level of physical fitness of students at SENIOR HIGH SCHOOL Negeri 8 Palembang. To achieve the best results, it is required to exercise. This quantitative research was designed with a descriptive design. A total of 316 class X students at SENIOR HIGH SCHOOL Negeri 8 Palembang were research subjects. The Indonesian Student Fitness Test (TKPN) was used in this research to measure students physical fitness levels. The data analysis method is descriptive presentation. The tests carried out are v sit and reach, endurance, abdominal muscle strength, body control, balance, coordination and agility. The results of the research show that the Indonesian Student Fitness Test (TKPN) of SENIOR HIGH SCHOOL Negeri 8 Palembang students is in the good category 0 people (0%), good 0 people (0%), fair 38 people (12,0%), less than 278 people (87,9%), and less than 0 people (0%). The research results show that students at SENIOR HIGH SCHOOL Negeri 8 Palembang have a low level of physical fitness. The research results show that the Indonesian Student Fitness Test (TKPN) can be useful for teachers to measure how well students learn at school, especially regarding physical education, sports and health. The results show that students’ physical fitness is related to academic and non-academic learning outcomes.